Association of the barriers of pharmaceutical care perceived by clinical pharmacists and occupational stress in tertiary hospitals of China - Zhang, Yu; Huang, Yuankai; Xi, Xiaoyu (Frontiers in Public Health, 2024)
Objective As an important member of the healthcare team, clinical pharmacists’ occupational stress will lead to a decline in the quality of pharmaceutical care. According to person-environment fit theory, barriers of pharmaceutical care perceived by clinical pharmacists may be a potential factor influencing occupational stress. This study aimed to assess the association between the specific barriers of pharmaceutical care perceived by clinical pharmacists and their occupational stress in China. Method A field-based questionnaire survey of tertiary hospitals was conducted in 31 provincial administrative regions in mainland China using a multi-stage stratified sampling method. Data on occupational stress, barriers of pharmaceutical care perceived by clinical pharmacists and other factors of job stress were collected using the Brief Job Stress Questionnaire and a self-administered instrument. The instruments have undergone multiple rounds of pilot investigations, and their reliability is acceptable. Ordinary least squares regression was used to evaluate the association of the perceived barriers and other factors with their occupational stress. Result A total of 625 clinical pharmacists from 311 tertiary hospitals in China (response rate = 84%) participated. Perceived resource dimension barriers (p = 0.00) and self-improvement dimension barriers (p = 0.01) were associated with increased occupational stress of the participants. In addition, clinical pharmacists with senior professional titles and engaged in neurology and ICU have higher occupational stress. Conclusion By removing barriers to pharmacists’ resources and self-improvement, it is possible to better meet the work needs of clinical pharmacists and may effectively reduce occupational stress, thereby improving the quality of pharmaceutical services.